A nanotechnological approach in the current therapy of COVID-19: model drug oseltamivir-phosphate loaded PLGA nanoparticles targeted with spike protein binder peptide of SARS-CoV-2 - Ucar, Burcu; Acar, Tayfun; Arayici, Pelin Pelit; Derman, Serap (IOP Publishing Ltd, 2021)
Coronavirus disease 2019 (COVID-19) is today's most serious epidemic disease threatening the human race. The initial therapeutic approach of SARS-CoV-2 disease is based upon the binding the receptor-binding site of the spike protein to the host cell's ACE-2 receptor on the plasma membrane. In this study, it is aimed to develop a biocompatible and biodegradable polymeric drug delivery system that is targeted to the relevant receptor binding site and provides controlled drug release. Oseltamivir phosphate (OP) is an orally administered antiviral prodrug for primary therapy of the disease in biochemically activated carboxylate form (oseltamivir carboxylate OC). In the presented study, model drug OP loaded poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) targeted with spike-binding peptide 1 (SBP1) of SARS-CoV-2 were designed to be used as an efficient and prolonged released antiviral drug delivery system. RY, EE, and DL values of the OP-loaded NPs produced by the solvent evaporation method were calculated to be 59.3%, 61.4%, and 26.9%, respectively. The particle size of OP-loaded NPs and OP-loaded NPs targeted with SBP1 peptide were 162.0 +/- 11.0 and 226.9 +/- 21.4 nm, respectively. While the zeta potential of the produced OP-loaded NPs was achieved negatively -23.9 +/- 1.21 mV), the result of the modification with SBP1 peptide this value approached zero as -4.59 +/- 0.728 mV. Morphological features of the OP-loaded NPs were evaluated using FEG-SEM. The further characterization and surface modification of the NPs were analyzed by FT-IR. In-vitro release studies of NPs showed that sustained release of OP occurred for two months that fitting the Higuchi kinetic model. By evaluating these outputs, it was reported that surface modification of OP-loaded NPs was significantly effective on characteristics such as size, zeta potential values, surface functionality, and release behavior. The therapeutic model drug-loaded polymeric formulation targeted with a specific peptide may serve as an alternative to more effective and controlled release pharmaceuticals in the treatment of COVID-19 upon an extensive investigation.
Keywords: COVID-19; SARS-CoV-2; oseltamivir; SBP1 peptide; PLGA nanoparticles; solid-phase peptide synthesis; DELIVERY; VIRUS; MECHANISMS; STABILITY; DESIGN; Science & Technology - Other Topics; Materials Science; Physics